2015
DOI: 10.1590/s0036-46652015000100012
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFICATION OF Pseudomonas spp. AS AMOEBA-RESISTANT MICROORGANISMS IN ISOLATES OF Acanthamoeba

Abstract: Acanthamoeba is a “Trojan horse” of the microbial world. The aim of this study was to identify the presence of Pseudomonas as an amoeba-resistant microorganism in 12 isolates of Acanthamoeba. All isolates showed the genus Pseudomonas spp. as amoeba-resistant microorganisms. Thus, one can see that the Acanthamoeba isolates studied are hosts of Pseudomonas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 17 publications
5
30
0
2
Order By: Relevance
“…Pseudomonas spp. are highly adaptable bacteria that have the ability to colonize various environmental niches (José Maschio et al 2015). Few of them evolved their ability and were able to survive predation by amoeba as supported in previous study by Siddiqui and Khan (2012) where Pseudomonas aeruginosa were reported to be naturally presence in Acanthamoeba and was proven in this study, as well.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Pseudomonas spp. are highly adaptable bacteria that have the ability to colonize various environmental niches (José Maschio et al 2015). Few of them evolved their ability and were able to survive predation by amoeba as supported in previous study by Siddiqui and Khan (2012) where Pseudomonas aeruginosa were reported to be naturally presence in Acanthamoeba and was proven in this study, as well.…”
Section: Discussionsupporting
confidence: 78%
“…Few of them evolved their ability and were able to survive predation by amoeba as supported in previous study by Siddiqui and Khan (2012) where Pseudomonas aeruginosa were reported to be naturally presence in Acanthamoeba and was proven in this study, as well. One of the reasons that led to this association is the presence of biofilm, where it plays a major role in the pathogenesis of Acanthamoeba keratitis as its provide attractive niches for both Acanthamoeba and bacteria especially in contaminated contact lens storage in keratitis cases (Khan 2006;José Maschio et al 2015). The interaction between Acanthamoeba and other microbial agents caused a great concern in the ability of this amoeba to indirectly transport a pathogen from the environment to humans including possible effects of their interactions on the virulence and pathogenicity of both organisms in human infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these studies did not identify these intra-amoebal bacteria at the species level. Co-culture studies with Acanthamoeba or Vermamoeba showed the ability of S. maltophilia and P. aeruginosa to resist amoebal digestion and multiply inside (Marolda et al 1999;Cateau et al 2014;José Maschio et al 2015). Our data then clearly confirmed the potential presence of these pathogens associated with FLA. Those reports are of public health concern as both species can be responsible of both nosocomial and community-acquired infections (Looney et al 2009;Mariappan et al 2013;Winstanley et al 2015).…”
Section: Discussionsupporting
confidence: 69%
“…The isolation of FLA naturally infected with Ps. aeruginosa [5,[26][27][28][29] demonstrated the role of amoebae and their cysts as vectors for these intracellular bacteria [30]. Our results showed the intracellular multiplication of Ps.…”
Section: Co-culture Of a Spelaea And Bacteriasupporting
confidence: 55%